KONFLIK KEPENTINGAN DIBALIK KONSERVASI STUDI DI TAMAN NASIONAL KERINCI SEBLAT (TNKS) PROVINSI JAMBI - Kausar ' (Indonesian Journal of Agricultural Economics, 2010)
The existence of conservation areas in Indonesia turned out to have caused lots ofproblems and conflict with society, especially local communities around theconservation area. Similarly, conservation areas of TNKS can not be separated from theconflicts of interest from various parties around the area. Therefore, this study tried toinvolve how conflicts of interest that occur within the conservation area of TNKS. Inthis research the method was descriptive while the approach used was qualitativeresearch. Research location was in Kerinci regency, Jambi Province, where more than50% of this area is the territory of TNKS region. The collecting of key informans usedpurposive sampling where respondents were drawn from those who know about theTNKS conflict and involved in the conflict. Based on research, there are many parties orstakeholders in the conflict, namely the conflict between the interests ofglobal/international and inside Indonesia, conflicts of central and local governments inthe management of conservation areas, and conflicts between the countries and people.So actually behind the conservation there is hidden conflict of interest from variousparties. Alternative solutions which need to be applied is to accommodate the interestsof each party, as well as to take steps to preserve the integrity of the conservation area.